Reflections on the relation between conservation and science - Antonio Iaccarino Idelson (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Problem solving in Conservation is made more complex by the difficulty of grounding on scientifically reliable data, and this issue is fundamental for the profession. The specific characteristics of thinking used in Conservation are compared to those of medicine and architecture. The evolution of Conservation and that of Conservation Science, sharing, exchange and production of information and knowledge are discussed. An outlook on Italian specificity is given, with the aim of favoring discussion on these vital subjects.